Evaluation of LUTS of the filling phase after Aquablation: A prospective single center experience - De Cillis, Sabrina; Amparore, Daniele; Quarà, Alberto; Checcucci, Enrico; Piana, Alberto; Volpi, Gabriele; Piramide, Federico; Sica, Michele; Ortenzi, Michele; Manfredi, Matteo; Di Dio, Michele; De Luca, Stefano; et al. (Frontiers in Urology, 2022)
Introduction: The aim of this study is to assess our first clinical experience with Aquablation in terms of perioperative and 1-year minctional outcomes, with focus on postoperative LUTS. Materials and methods: From 10/2018 to 07/2021, patient referred to our center with BPH-related LUTS, International Prostate Symptom Score (IPSS) ≥10, maximum urinary flow rate (Qmax) ≤12 mL/ s, and prostate volume <80 mL were enrolled in this prospective study to undergo Aquablation. Demographics, perioperative data and complications (according to the Clavien–Dindo system) were collected. Functional outcomes were assessed at 1, 3, 6, and 12 months with IPSS, IPSS quality of life (IPSS QoL), uroflowmetry and evaluation of post void residue (PVR). Type of LUTS were classified on the bases of IPSS single questions answers in filling phase LUTS and voiding phase LUTS. Results: 60 patients were enrolled in the study. The mean (SD) patient age was 64.9 (7.3) years, prostate volume was 63.5 (16.8) mL, Qmax was 8.4 (2.6) mL/s, median (IQR) IPSS was 23 (19-26), and IPSS QoL score was 5 (4–5). The mean (SD) Qmax at 1, 3, 6 and 12 months was 21.1 (11), 18.1 (5.4), 17.1 (6) and 17.8 (6.6) ml/s, respectively. The median IPSS urinary symptom score was 2 (2-5) one year after surgery. In parallel, the median IPSS QoL score and mean PVR reached 1 (0- 1) and 23.6 ml (25.5) at 12th month. At 1- and 3-months follow-up, filling phase symptoms showed to be predominant in almost two third of study population. 27 out of 38 (71%) patients with a prevalence of filling phase symptoms at 3 months reported a de novo onset of these symptoms after surgery. Conclusion: Aquablation is a safe procedure for the treatment of BPH related LUTS, and it demonstrated to be effective up to 1-year follow up. LUTS of the filling phase were more prevalent than voiding phase ones in the first 3 -months following surgeries, but showed a self-limited fashion.